Answer
To eliminate x, we will multiply the second equatio by -3.
x = 7
y = 5
Step-by-step explanation
To solve this, we first write the two equations
-3x - 7y = -56
-7x + 10y = 1
So, to solve this, we need to make sure the factors of x are the same numbers and of opposite signs
So, if we multiply the first equation by 7, we will need to multiply the second equation by -3 to obtain 21x and -21x for the two of them.
(-3x - 7y = -56) × 7
(-7x + 10y = 1) × -3
-21x - 49y = -392
21x - 30y = -3
We will then add the two equations and then the solution for the equation is obtained by solving for y first.
-21x + 21x - 49y - 30y = -392 - 3
0 - 79y = -395
-79y = -395
Divide both sides by -79
(-79y/-79) = (-395/-79)
y = 5
We can then solve for x using any of the two equations
-7x + 10y = 1
-7x + 10(5) = 1
-7x + 50 = 1
-7x = 1 - 50
-7x = -49
Divide both sides by -7
(-7x/-7) = (-49/-7)
x = 7
Hope this Helps!!!